2020
DOI: 10.1007/s10815-020-01697-7
|View full text |Cite
|
Sign up to set email alerts
|

Testicular sperm extraction and intracytoplasmic sperm injection outcome in cancer survivors with no available cryopreserved sperm

Abstract: Objective To assess rates of successful testicular sperm retrieval and intracytoplasmic sperm injection (ICSI) outcome in cancer survivors affected by non-obstructive azoospermia (NOA) or retrograde ejaculation (RE)/failure of emission (FOE). Methods A retrospective analysis of cancer survivors who did not cryopreserve sperm prior to treatment undergoing testicular sperm extraction (TESE). Non-cancer NOA patients and neurologic RE/FOE were the control group. Results A total of 97 cancer survivors were offered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Eleven retrospective studies 26 29 30 31 32 33 34 35 36 37 38 and 8 case reports or case series 39 40 41 42 43 44 45 46 reported results for postgonadotoxic treatment TESE. The case reports and case series mainly reported TESEs that allowed for spermatozoa retrieval, while the retrospective studies reported between 33.3% and 76.2% positive TESEs ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Eleven retrospective studies 26 29 30 31 32 33 34 35 36 37 38 and 8 case reports or case series 39 40 41 42 43 44 45 46 reported results for postgonadotoxic treatment TESE. The case reports and case series mainly reported TESEs that allowed for spermatozoa retrieval, while the retrospective studies reported between 33.3% and 76.2% positive TESEs ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…In these cases of nonobstructive azoospermia, testicular sperm extraction via microdissection can yield sperm for IVF with ICSI. Single center experiences report successful surgical sperm retrieval rates of 37%–44% per patient and live birth rate of 40%–59% per couple 89,90 . Thus, a finding of azoospermia warrants a referral to reproductive urologists for the possibility of surgical sperm extraction to use autologous gametes.…”
Section: Post‐treatment Considerationsmentioning
confidence: 99%
“… 20 When completed by intracytoplasmatic sperm injection (ICSI), live birth rates following TESE in cancer patients are 40% per couple per single ovarian hyperstimulation. 21 Therefore, in the event of azoospermia or if sperm banking is not possible, testicular tissue cryopreservation for TESE can be an effective FP option. 21 …”
Section: Introductionmentioning
confidence: 99%
“… 21 Therefore, in the event of azoospermia or if sperm banking is not possible, testicular tissue cryopreservation for TESE can be an effective FP option. 21 …”
Section: Introductionmentioning
confidence: 99%